How Intelligence Can Be a Solution to Consequential World Problems - Sternberg, Robert J.; Conway, Andrew; Halpern, Diane (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Intelligence research is mainly concerned with basic science questions; what is the psychometric structure of intelligence? What are the cognitive bases of intelligence? What are the brain-based correlates of intelligence? What does intelligence predict? Such research is needed, but there are also problems larger than those presented in intelligence tests, including problems of today. What is the role of human intelligence in solving consequential real-world problems? Here, leading scholars in the field of intelligence each address one real-world problem-a problem of their choice-and explain how intelligence has been, or could be, essential for a solution.